Neoproterozoic mafic complex in the Bikou microblock on the northwestern Yangtze Block: Implications for mantle source and tectonic evolution - Li Qin; Xianzhi Pei; Ruibao Li; Lei Pei; Chengjun Liu; Zuochen Li; Shaowei Zhao; Feng Gao (Lithos, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Ionic/hydrogen-bonding dual-network orchestration in sulfonated-OPBI via phytic acid-PEI nanoarchitectonics of PAFs for efficient proton transfer highways - Fei Chen; Xinyi Zong; Xianfeng Guan; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Nanofiber ionic bridge framed quasi-solid polymer electrolyte with nanocellulose and PAF for improved low-temperature lithium battery - Jiayi Luo; Shenyuan Li; Yangyang Yu; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Evolution of cracks in red-bed mudstone under the coupling of drying-wetting cycle and temperature: From microscopic mechanism to a kinetic model - Guodong Zhang; Sixiang Ling; Chengjun Xiao; Hongwei Liu; Xiaoning Li; Rui Deng; Xiyong Wu (Engineering Geology, 2026)

Unraveling microscopic dielectric response of liquid-liquid phase separation via electrochemical impedance spectroscopy combined with distribution of relaxation times - Jie He; Jinming Liang; Kai Liu; Bai Chen; Wanyi Ye; Xiuli Wu; Siqi Zhu; Zhenqiang Chen; Chengjun Zhu; Jiafeng Yao (Chemical Engineering Journal, 2026)

Migration and transformation of antimony during Fe(II)-induced ferrihydrite recrystallization under anaerobic conditions - Chengjun Zhang; Mengchang He; Huiji Liu; Matthew I. Leybourne; Tangfu Xiao (Applied Geochemistry, 2026)

Field monitoring and numerical analysis of a novel micro-disturbance partial freezing technology: A case study of the first Bangkok power tunnel rehabilitation project in Thailand - Jie Zhou; Huade Zhou; Chengjun Liu; Chao Ban; Hsinming Shang; Lei Huang (Tunnelling and Underground Space Technology, 2026)

Synthesis of hydroxyapatite coating material from waste steelmaking slag - Xueying Chen; Qing Zhao; Wenran Xia; Mengjie Tao; Xiaohui Mei; Chengjun Liu; Henrik Saxén; Ron Zevenhoven (Journal of Environmental Chemical Engineering, 2026)

Thermal-hydraulic coupling effects on shear strength and particle breakage of coral sand - Jie Zhou; Huade Zhou; Xiangzhen Kong; Chao Ban; Chengjun Liu; Zhenming Shi (Marine Georesources & Geotechnology, 2026)

Multi-objective optimization for hydrofoil cavitation erosion resistance based on cumulative impact energy indicator - Bingru Lan; Chengjun Shan; Lizhe Yi; Mengru Liu; Chao Ou; Yaosong Long (Ocean Engineering, 2026)

Recovery of niobium, titanium and iron from Bayan Obo polymetallic associated ore based on hydrogen reduction and oxalic acid leaching - Xingli Jia; Bo Zhang; Zhongshuai Jia; Jingwen Luo; Chengjun Liu; Maofa Jiang (Hydrometallurgy, 2026)

Release of antimony from Sb(V) incorporated iron oxides during oxalate-promoted recrystallization under aerobic conditions - Chengjun Zhang; Mengchang He; Tangfu Xiao; Huiji Liu (Environmental Research, 2026)

Physics-based digital twin system for artificial ground freezing: implementation in Bangkok tunnel rehabilitation - Jie Zhou; Chengjun Liu; Chao Ban; Zhenming Shi; Hsinming Shang; Huade Zhou; Zeyao Li (Tunnelling and Underground Space Technology, 2026)

Offshore wind monopile bearing capacity prediction method based on CPTU: Research on the axial bearing mechanism by CPTU - Jie Zhou; Chengjun Liu; Zhenming Shi; Panpan Shen; Yingkang Zhong (Ocean Engineering, 2026)

The photo-release of dissolved organic matter from soil-derived sources: An insight into the impact of acid mine drainage - Lezhang Wei; Fangqing Li; Yu Liu; Qihang Wu; Chengjun Zhang; Xuexia Huang; Dinggui Luo; Juan Liu; Tangfu Xiao (Journal of Environmental Sciences, 2026)

Critical bistability in variable cross-section metamaterials: PINN-driven transient stress recognition and adaptive energy dissipation - Jian Zhou; Chengjun Zeng; Wei Zhao; Jinsong Leng; Yanju Liu (Chemical Engineering Journal, 2026)

Effects of organic mulching on soil aggregates, main microbial groups, and enzyme activity in Chinese hickory plantation - Chenfei Liang; Qian Liu; Chengjun Wang; Junhui Chen; Shuai Shao; Liang Wang; Caixia Liu (Biology and Fertility of Soils, 2026)

Early Devonian alkaline volcanism in the North Qaidam, NW China: Insights into the Proto- to Paleo-Tethys tectonic transition - Mao Wang; Xianzhi Pei; Lei Pei; Zuochen Li; Chengjun Liu; Lili Xu; Ruibao Li; Li Qin; Xiao Wang; Nan Hu; Hao Lin (Journal of Asian Earth Sciences, 2026)

Tonian intra-oceanic subduction initiation at the northwestern Yangtze Block: Evidence from forearc ophiolite fragments in the Bikou microblock - Li Qin; Xianzhi Pei; Ruibao Li; Lei Pei; Chengjun Liu; Zuochen Li; Shaowei Zhao; Feng Gao (Precambrian Research, 2026)

Multi-stage tectono-magmatic evolution of the Proto-Tethys Ocean: Constraints from Mid-Paleozoic granitoids in the East Kunlun-North Qaidam orogenic belt - Mao Wang; Xianzhi Pei; Lei Pei; Ruibao Li; Zuochen Li; Chengjun Liu; Youxin Chen; Nan Hu; Li Qin; Xiao Wang (Gondwana Research, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

Effects of ocean acidification on intestinal homeostasis and organismal performance in a marine bivalve: From microbial shifts to physiological suppression - Minggui Liu; Xiaoyu Guo; Lanfang Han; Yuanyuan Zhao; Chengjun Ge (Marine Pollution Bulletin, 2026)

Mixed deciduous-evergreen needleleaf forests across China can be regarded as a separate vegetation type - Rongzhen Yuan; Zhiping Wang; Zhiyao Tang; Wenjing Fang; Chunyun Liu; Chengjun Ji; Qinggui Wang; Ming Yue; Guohong Wang (Plant Ecology, 2026)

Recovery of niobium, titanium and rare earths from Bayan Obo tailings via silicothermic reduction and targeted crystallization - Xingli Jia; Bo Zhang; Zhongshuai Jia; Chengjun Liu; Maofa Jiang (Minerals Engineering, 2025)

Ready-to-eat beef steaks prepared by superheated steam: from texture and flavor to storage stability - Jiyuan He; Lunzhou Lin; Jiebin Cai; Chengjun Liu; Yaming Xiao; Yajie Shen; Binxiong Liu; Ting Fang (International Journal of Gastronomy and Food Science, 2025)

Orthotropic steel deck reinforcement technique for super-long span bridges with thin dense-reinforced UHPC Layers - Zihao Luo; Chengjun Tan; Junhui Cao; Kun Liu; Sui Luo; Jiahe An; Hua Zhao; Xudong Shao; Dutao Yi (Engineering Structures, 2025)

Quantitative analysis of standard penetration rate and interference distance of centrifuge CPTU: an attempt for CPTU-based prediction method in offshore monopile bearing capacity - Jie Zhou; Chengjun Liu; Zhenming Shi; Panpan Shen (Ocean Engineering, 2025)

Distribution characteristics of black carbon in Taihu Lake sediments and their effects on microorganisms - Yan Li; Hang Su; Ke Liu; Chengjun Ge; Qingkun Wang; Xinyu Cheng; Jiang Jiang (Environmental Research, 2025)

Numerical study of helium bubble behavior and its effect on heat transfer of liquid lithium on an inclined wall - Wenchao Zhang; Yan Nie; Chengjun Long; Gongqing Wang; Chao Liu; Benan Cai; Weihua Cai (Annals of Nuclear Energy, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

METTL3-mediated modification of SIRT1 m6A methylation protects osteoblasts from TBHP-induced senescence and promotes osteoblast proliferation - Yi Chen; Yaobin Wang; Hefang Xiao; Fei Teng; Ao Yang; Jinmin Liu; Zirui Liu; Xiaoyun Sheng; Chengjun Zhang; Shifeng Zhang; Bin Geng; Yayi Xia (Chemico-Biological Interactions, 2025)

Estimation of Genetic Parameters for Hypoxia Tolerance in the Pacific Oyster, Crassostrea gigas - Mengmeng Xu; Ben Yang; Xiaojie Han; Deqi Sun; Chao Guo; Chengjun Zhi; Qi Li; Shikai Liu (Journal of Ocean University of China, 2025)

Neural Network-Based Ship Power Load Forecasting - Haozheng Liu; Chengjun Qiu; Wei Qu; Wei He; Yuan Zhuang; Puze Li; Huili Hao; Wenhao Wang; Zizi Zhao; Jiahua Su (Journal of Marine Science and Engineering, 2025)
This study combines an experimental semi-physical simulation model of an electric propulsion tugboat with four different neural networks to create a real-time simulation model for forecasting total power loads with small samples. The results of repeated experiments demonstrate that the BP neural network effectively forecasts the power load. Subsequently, addressing the limitations of traditional BP neural networks, an optimization approach employing an enhanced particle swarm algorithm and attention mechanism was developed, thereby improving the model’s prediction accuracy and robustness. The experiment shows that the improved prediction model achieves an R2 value of 97.42%, demonstrating its effectiveness in forecasting changes in the short-term power load of ships as parameters change. In actual operation, ships can allocate power reasonably and in a timely manner according to the load forecast results, thereby improving the efficiency of the power grid.

5-Hydroxytryptamine mediated 5-HTR4-ILP axis orchestrates glucose utilization and glycogen storage in the Pacific oyster (Crassostrea gigas) - Liting Ren; Ben Yang; Mengmeng Xu; Chengjun Zhi; Qi Li; Shikai Liu (Food Bioscience, 2025)

4D printed kirigami metamaterial with reconfigurability for dual-mode displacement-pressure sensing - Song Liu; Zhaoxuan Niu; Wei Zhao; Chengjun Zeng; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2025)

Evolution characterization of moisture migration and pressure-melting of artificially frozen soft soil based on low-temperature triaxial seepage MRI system - Jie Zhou; Huade Zhou; Chao Ban; Zhenming Shi; Chengjun Liu; Lujia Chen (Cold Regions Science and Technology, 2025)

Crystallization behavior of calcium silicate phases in molten steelmaking slag - Mengjie Tao; Qing Zhao; Zengrui Wang; Chengjun Liu; Henrik Saxén; Ron Zevenhoven (Journal of Environmental Management, 2025)

Occurrence, hydrolysis and photodegradation of phthalate esters in urban atmospheric aqueous aerosol in Wuhan City - Xinyue Zhao; Siyu Liu; Lina Wang; Li Yang; Jun He; Chengjun Wang (Environmental Pollution, 2025)

Fast decomposition of typical endocrine disturbing compounds in microdroplets under sunlight irradiation in the presence of ozone - Siyu Liu; Xinyue Zhao; Yaobin Ding; Lina Wang; Yiyang Li; Jun He; Chengjun Wang (Chemosphere, 2025)

Mycorrhizal association shapes responses of plant biomass but not soil carbon to nitrogen addition in global forests - Danhua Zhang; Suhui Ma; Xuemei Yang; Erhan Huang; Chen Yang; Kai Dong; Lingli Liu; Biao Zhu; Zhiyao Tang; Chengjun Ji; Jiangling Zhu; Jingyun Fang (Forest Ecology and Management, 2025)

Chemical and field-effect passivation coupling for performance enhancement of inverted wide-bandgap perovskite solar cells - Jiali Wei; Xin Wang; Kai Wu; Zhuyou Liu; Jingwei Guo; Haoran Yang; Tiantian Li; Chengjun Zhu; Fuhua Hou (Chemical Engineering Journal, 2025)

Genetic Basis of Low-Salinity Tolerance in the Pacific Oyster (Crassostrea gigas) as Revealed by Estimation of Genetic Parameters and Genome-Wide Association Study - Xiaojie Han; Ben Yang; Chao Guo; Mengmeng Xu; Deqi Sun; Chengjun Zhi; Qi Li; Shikai Liu (Marine Biotechnology, 2025)

pH-responsive color indicator film based on gelatin/chitosan cross-linking with anthocyanin-Fe2+ chelate for pork freshness monitoring - Haolan Zhao; Wei Liu; Chengjun Min; Yuxia Qi; Xiangning Chen; Hongru Zhang (Food Hydrocolloids, 2025)

Detachment fault system in the Zedang ophiolite of southern Tibet: New insights into the evolution of the neo-Tethys ocean - Yuan Li; Ruibao Li; Chengjun Liu; Jian Zhang; Duoji Ciren; Xiao Zhou; Zhenkai He; Jingsui Yang (Journal of Asian Earth Sciences, 2025)

COVID-19 and acute limb ischemia: latest hypotheses of pathophysiology and molecular mechanisms - Chengjun Yao; Yanzhao Dong; Haiying Zhou; Xiaodi Zou; Ahmad Alhaskawi; Sohaib Hasan Abdullah Ezzi; Zewei Wang; Jingtian Lai; Vishnu Goutham Kota; Mohamed Hasan Abdulla Hasan Abdulla; Zhenfeng Liu; Sahar Ahmed Abdalbary; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

High-Resolution 3D Shear-Wave velocity structure in xiong’an New Area, Beijing (China), revealed by short-period dense seismic array - Qiaoxia Liu; Zhiping Xu; Ming Zhou; Yonghong Duan; Yong Qiu; Chengjun Feng; Shuaipeng Zhu; Chongpeng Wang; Minjie Chen (Journal of Asian Earth Sciences, 2025)

Construction of a novel BaZr0.1Ce0.7Y0.2O3-δ-SnO2 heterojunction composite electrolyte for advanced semiconductor ion fuel cells operating at lower temperature down to 350 ℃ - Decai Zhu; Zhongqing Liu; Chengjun Zhu; Yingbo Zhang; Jiangyu Yu; Jiamei Liu; Yuzhao Ouyang; Jie Yu; Nan Wang; Yaohui Niu; Jiali Zhou (Chemical Engineering Journal, 2025)

CPTU-Based Offshore Wind Monopile Rigid Bearing Mechanism Analysis - Jie Zhou; Renjie Gu; Panpan Shen; Chengjun Liu; Zeyao Li; Kefan Zhu; Zhenming Shi (Journal of Marine Science and Engineering, 2025)
With the development of the offshore wind industry in China, the amount of offshore wind turbines has increased rapidly. Large-diameter steel monopile foundations of offshore wind turbines have been widely adopted in China with lots of marine clay located. However, the conventional offshore wind monopile bearing capacity prediction from the American Petroleum Institute (API) based on the small-diameter flexible pile field test is inaccurate with the rigid mechanism of large-diameter monopile causing economically loss. The piezocone penetration test (CPTU) is a common marine in situ test to exactly acquire soil parameters. Therefore, a CPTU-based offshore wind monopile rigid mechanism inference method is proposed. A creative numerical offshore wind power monopile and CPTU combined model is established through COMSOL. A self-compiling parameter function is applied to soil modeling and an innovative mobile boundary function is created to simulate CPTU penetration. Through the model, real-time CPTU data can be acquired when monopile is applied with different horizontal loads. The peripile soil stress change can be timely detected by CPTU. Through CPTU data, the monopile rigid bearing mechanism is verified. A rigid rotation center is found at the 60% point of the inserted monopile. The method is an important foundation for the next step of monopile bearing capacity research.

4D printed mortise-tenon mechanical-electromagnetic multifunctional pixel metamaterials - Xiaozhou Xin; Chunli Yang; Zhicheng Wang; Yin Xing; Chengjun Zeng; Liwu Liu; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2025)

SnS-induced element diffusion Simultaneous optimization of interface and bulk defects in High-Efficiency CZTSSe solar cells - Chenjun Yang; Letu Siqin; Yutian Wang; Yufei Li; Wenbo Li; Shuyu Li; Ruijian Liu; Hongmei Luan; Chengjun Zhu (Chemical Engineering Journal, 2025)

Nitrogen addition promotes soil carbon accumulation globally - Xuemei Yang; Suhui Ma; Erhan Huang; Danhua Zhang; Guoping Chen; Jiangling Zhu; Chengjun Ji; Biao Zhu; Lingli Liu; Jingyun Fang (Science China Life Sciences, 2025)

Chronic exposure to hexavalent chromium induces esophageal tumorigenesis via activating the Notch signaling pathway - Yilin Zhu; Fanrong Liu; Lei Liu; Jinfu Wang; Fengyuan Gao; Lan Ye; Honglei Wu; Chengjun Zhou; Guimei Lin; Xiaogang Zhao; Peichao Li (Journal of Zhejiang University-SCIENCE B, 2025)

Coseismic surface deformation and source mechanism of the 2023 Ms 6.2 Jishishan earthquake, northeastern Tibetan Plateau - Peng Chen; Siqi Shu; Zhonghai Wu; Tao Wang; Chengjun Feng; Jiamei Liu; Shuai Zhang; Haojie Wang; Kun Li (Journal of Structural Geology, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Crystallization behavior of BOF slag during the cooling process towards leaching for CO2 sequestration - Xiaohui Mei; Qing Zhao; Chengzhi Han; Zengrui Wang; Yi Min; Chengjun Liu; Henrik Saxén; Ron Zevenhoven (Process Safety and Environmental Protection, 2024)

Estimating the spatiotemporal distribution of PM2.5 concentrations in Tianjin during the Chinese Spring Festival: Impact of fireworks ban - Zhifei Liu; Kang Zheng; Shuai Bao; Yide Cui; Yirong Yuan; Chengjun Ge; Yixuan Zhang (Environmental Pollution, 2024)

Electrically conductive functionalization of cured polyether ether ketone with improved bioactivity by surface-polymerization of polyaniline - Xuelian Wu; Yang Zhou; Jian Yang; Xiongjie Liang; Yuanrong Xin; Qian Yang; Guanghua Chen; Chengjun Zeng; Xin Lan; Wei Zhao; Yanju Liu (Chemical Engineering Journal, 2024)

Shear behavior on PBL shear connector with a relatively thin perforated steel plate in steel-UHPC composite bridge deck system - Zihao Luo; Hua Zhao; Dongqin Qiao; Yufei Zhang; Jiahe An; Chengjun Tan; Linong Liang; Anxing Liu; Xudong Shao (Engineering Structures, 2024)

Precipitation nowcasting leveraging spatial correlation feature extraction and deep spatio-temporal fusion network - Wenbin Yu; Yangsong Li; Cheng Fan; Daoyong Fu; Chengjun Zhang; Yadang Chen; Ming Qian; Jie Liu; Gaoping Liu (Earth Science Informatics, 2024)

Designing of low-temperature high performance semiconductor ionic fuel cells based on molten hydroxide percolation network - Yingbo Zhang; Decai Zhu; Chengjun Zhu; Jiamei Liu; Jiangyu Yu; Zhongqing Liu; Xixi Bai; Nan Wang; Yaohui Niu; Jiali Zhou (Chemical Engineering Journal, 2024)

Mineral phase reconstruction of Bayan Obo tailings by smelting reduction and crystallization control of molten slag containing niobium, rare earth and titanium - Bo Zhang; Jiafan Liu; Xingli Jia; Tong Xing; Chengjun Liu; Maofa Jiang (Minerals Engineering, 2024)

Polystyrene microplastics exposure reduces meat quality and disturbs skeletal muscle angiogenesis via thrombospondin 1 - Yun Yang; Hu Liu; Dongbin Zou; Fengjie Ji; Renlong Lv; Hongzhi Wu; Hanlin Zhou; Ao Ren; Tieshan Xu; Guanyu Hou; Chengjun Hu (Food Research International, 2024)

Forecasting daily PM2.5 concentrations in Wuhan with a spatial-autocorrelation-based long short-term memory model - Zhifei Liu; Chengjun Ge; Kang Zheng; Shuai Bao; Yide Cui; Yirong Yuan; Yixuan Zhang (Atmospheric Environment, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Detrital Zircon Geochronology of Early Triassic Strata in the West Qinling Orogen: Implications for the Tectonic Evolution of the Paleo-Tethyan Ocean - Zuochen Li; Xianzhi Pei; Liyong Wei; Guobing Liang; Meng Wang; Ruibao Li; Lei Pei; Chengjun Liu; Youxin Chen; Feng Gao (Journal of Earth Science, 2024)

Auto-adjustment label assignment-based convolutional neural network for oriented wheat diseases detection - Haiyun Liu; Hongbo Chen; Jianming Du; Chengjun Xie; Qiong Zhou; Rujing Wang; Lin Jiao (Computers and Electronics in Agriculture, 2024)

Effectiveness of natural ventilation through single-sided window opening in air-conditioning rooms - Xinyu Liu; Hanqing Wang; Zhengming Li; Jinping Zhao; Chengjun Li; Dong Xie (Energy and Buildings, 2024)

Mercury supply limits methylmercury production in paddy soils - Huan Zhong; Yao Su; Xinda Wu; Luís Nunes; Chengjun Li; Yunyun Hao; Yu-Rong Liu; Wenli Tang (Science of The Total Environment, 2024)

Practical four-electron zinc-iodine aqueous batteries enabled by orbital hybridization induced adsorption-catalysis - Tingting Liu; Chengjun Lei; Huijian Wang; Chen Xu; Wenjiao Ma; Xin He; Xiao Liang (Science Bulletin, 2024)

Origin of granitoids and coeval mafic microgranular enclaves in the East Kunlun Orogen, northern Tibetan Plateau: Insights from petrography, U-Pb geochronology, geochemical and isotope analyses - Guochao Chen; Xianzhi Pei; Ruibao Li; Zuochen Li; Lei Pei; Chengjun Liu; Youxin Chen (Journal of Asian Earth Sciences, 2024)

A novel photoelectrochemical self-screening aptamer biosensor based on CAU-17-derived Bi2WO6/Bi2S3 for rapid detection of quorum sensing signal molecules - Shiliang Wang; Peng Ju; Weixing Liu; Jingtian Chi; Tiantong Jiang; Zhe Chi; Shuai Wang; Ri Qiu; Chengjun Sun (Analytica Chimica Acta, 2024)

Genomic selection accelerates genetic improvement of resistance to Vibriosis in the Pacific oyster, Crassostrea gigas - Ben Yang; Chengjun Zhi; Pengfei Li; Chengxun Xu; Qi Li; Shikai Liu (Aquaculture, 2024)

Macroscopic behaviour and mesoscopic mechanism of shear strength characteristics of pile-soil interface under cyclic loading - Jie Zhou; Chengjun Liu; Kefan Zhu; Panpan Shen (Ocean Engineering, 2024)

Mineral resource management in Chinese rural areas: Policy assessment for green economic growth - Jin Xu; Chengjun Liu; Gang Dou; Yunfei Cai (Resources Policy, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Simulation of MJO with improved deep convection scheme in different resolutions of BCC-CSM2 models - Mengzhe Zheng; Tongwen Wu; Xiaoge Xin; Xiangwen Liu; Yixiong Lu; Weihua Jie; Chengjun Xie; Yumeng Zhou (Climate Dynamics, 2024)
This study investigates the impacts of modifying the deep convection scheme on the ability to simulate the Madden–Julian Oscillation (MJO) in the Beijing Climate Center Climate System Model version 2 with a medium resolution (BCC-CSM2-T159) and a high resolution (BCC-CSM2-T382). On the basis of the original deep convection scheme, a modified scheme is suggested, which involves the transport processes of deep convective cloud water. The liquid cloud water that is detrained is transferred horizontally to its neighboring grids, and a portion of the cloud water that is horizontally transported is allowed to be transported downward into the lower troposphere. Both BCC-CSM2-T159 and BCC-CSM2-T382 with the modified deep convection scheme perform better than that used the original deep convection scheme in reproducing the major features of the MJO, such as its spectrum, period, intensity, eastward propagation and life cycle. Further analysis shows that those pronounced improvements in the MJO features in both BCC-CSM2-T159 and BCC-CSM2-T382 with the modified scheme are caused by transport processes of deep convective cloud water. The modified deep convection scheme enhances moisture and energy exchange from the lower troposphere to the upper troposphere around convective cloud, and promotes the convergence of moisture in the lower troposphere to the east of the MJO convection center, and then induces eastward propagation of the MJO. The comparisons between the coupled experiments and their corresponding experiments following Atmospheric Model Intercomparison Project (AMIP) simulations indicated that atmosphere–ocean interactions are also important to improve MJO simulations in the models.

Low-molecular-weight organic acids-mediated transport of neonicotinoid pesticides through saturated soil porous media: Combined effects of the molecular structures of organic acids and the chemical properties of contaminants - Bingyao Xu; Lulu Lu; Mengya Liu; Qiang Zhang; Usman Farooq; Taotao Lu; Zhichong Qi; Chengjun Ge (Chemosphere, 2024)

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Preparation of leaf protoplasts from Populus (Populus × xiaohei T. S. Hwang et Liang) and establishment of transient expression system - Chengjun Yang; Ruiqiang Yu; Jinbo Li; Kai Wang; Guanjun Liu (Journal of Plant Physiology, 2023)

Regulation of electrical properties via ferroelectric polarization for high performance Sb2Te3 thermoelectric thin films - Boyu Yang; Yubo Luo; Chengjun Li; Wang Li; Chengwei Sun; Zheng Ma; Yongxin Qian; Xianwei Zeng; Yingchao Wei; Haiqiang Liu; Dan Zhang; Xin Li; et al. (Chemical Engineering Journal, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Black phosphorus nanosheets enhance differentiation of neural progenitor cells for improved treatment in spinal cord injury - Fumei He; Ke Cheng; Junyang Qi; Fangjie He; Chengjun Chu; Yue Xiong; Jingxin Zhao; JiaQi Ding; FanShu Kong; ZiMeng Cao; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Dissolution behavior of steelmaking slag for Ca extraction toward CO2 sequestration - Xiaohui Mei; Qing Zhao; Yi Min; Chengjun Liu; Peiyang Shi; Henrik Saxén; Ron Zevenhoven (Journal of Environmental Chemical Engineering, 2023)

Benefited wastewater utilization via configurable, spatialized, and microorganisms-integrated biophotonic systems - Yantong Liu; Longfei Chen; Le Yu; Jiaomeng Zhu; Fang Wang; Fenghua Jiang; Chengjun Sun; Li Zheng; Yi Yang (Chemical Engineering Journal, 2023)

Efficient ternary organic solar cells enabled by asymmetric nonfullerene electron acceptor with suppressed nonradiative recombination - Renjie Xu; Yuanyuan Jiang; Feng Liu; Wenli Su; Wuyue Liu; Shengjie Xu; Haijun Fan; Chengjun Jiang; Qianshou Zong; Wenkai Zhang; Xiaozhang Zhu (Chemical Engineering Journal, 2023)

R-loopAtlas: An integrated R-loop resource from 254 plant species sustained by a deep-learning-based tool - Kuan Li; Zhenzhen Wu; Jincong Zhou; Wei Xu; Ling Li; Chao Liu; Wei Li; Chengjun Zhang; Qianwen Sun (Molecular Plant, 2023)

Unraveling the joint toxicity of transition-metal dichalcogenides and per- and polyfluoroalkyl substances in aqueous mediums by experimentation, machine learning and molecular dynamics - Guohong Liu; Xiliang Yan; Chengjun Li; Song Hu; Jiachen Yan; Bing Yan (Journal of Hazardous Materials, 2023)

Magmatic response to the closure of the Proto-Tethys Ocean: A case study from the middle Paleozoic granitoids in the Kunlun Orogen, western China - Ruibao Li; Xianzhi Pei; Renjie Zhou; Zuochen Li; Lei Pei; Guochao Chen; Youxin Chen; Chengjun Liu (Journal of Asian Earth Sciences, 2023)

Intensified gas-phase hydrogenation of acetone to isopropanol catalyzed at metal-oxide interfacial sites - Kun Liu; Yongbin Sun; Jie Feng; Yang Liu; Jian Zhu; Chengjun Han; Changzhi Chen; Tianyi Bao; Xiaoqun Cao; Xiaomin Zhao; Yong Yang; Guofeng Zhao (Chemical Engineering Journal, 2023)

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

Research on the Karhunen–Loève Transform Method and Its Application to Hull Form Optimization - Haichao Chang; Chengjun Wang; Zuyuan Liu; Baiwei Feng; Chengsheng Zhan; Xide Cheng (Journal of Marine Science and Engineering, 2023)
Hull form optimization becomes prone to the curse of dimensionality as the number of design variables increases. The traditional sensitivity analysis method requires massive computational fluid dynamics (CFD) computations and analyzing the effects of all variables on the output; thus, it is extremely time-consuming. Considering this, the development of a rapid and effective dimensionality reduction method is particularly important. The Karhunen–Loève (K–L) transform method projects data from a high-dimensional space onto a low-dimensional space in the direction of the eigenvectors corresponding to large-variance eigenvalues. It extracts the principal components that represent the hull offset information to represent the hull geometric characteristics by analyzing the relationship between the variables in the sample offset matrix. The geometric information matrices of new hull forms can be rapidly reconstructed from the principal components. Compared with direct optimization methods, fewer variables are used to control the deformation of the hull form from the perspective of geometric deformation, avoid a large number of CFD calculations, and improve the efficiency of optimization. This study examined the relevant K–L matrix solution methods and the corresponding hull form reconstruction methods and proposed eigenvalue-based hull form reconstruction equations. The K–L transform method was combined with a previously developed multidisciplinary platform for a comprehensive optimization of ship hydrodynamic performance for hull form optimization, and its effectiveness was verified by using it to optimize DTMB 5415. The results showed that the K–L transform–based dimensionality reduction method significantly reduces the time consumption of optimization while maintaining an acceptable optimization performance.

Reconfigurable modular microbiota systems for efficient and sustainable water treatment - Longfei Chen; Yantong Liu; Pengfu Tian; Le Yu; Fang Wang; Hongshan Xu; Yifan Wang; Wei Li; Li Zheng; Fenghua Jiang; Chengjun Sun; Xuming Zhang; et al. (Chemical Engineering Journal, 2023)

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Interactive effects of high temperature and crude protein levels on growth performance, nitrogen excretion, and fecal characteristics of broilers - Quanwei Liu; Jinghai Feng; Limin Wei; Chengjun Hu; Xinli Zheng; Ruiping Sun; Minhong Zhang (Tropical Animal Health and Production, 2022)

Reaching the Full Potential of Machine Learning in Mitigating Environmental Impacts of Functional Materials - Ying He; Guohong Liu; Chengjun Li; Xiliang Yan (Reviews of Environmental Contamination and Toxicology, 2022)

Petrogenesis and tectonic setting of Early Silurian island-arc-type quartz diorite at the southern margin of the East Kunlun orogenic belt: analysis of the evolution of the Proto-Tethyan Ocean - Zuochen Li; Xianzhi Pei; Ruibao Li; Paul D. Bons; Lei Pei; Youxin Chen; Chengjun Liu; Meng Wang; Shaowei Zhao; Guochao Chen; Hai Zhou; Jie Zhao; et al. (International Journal of Earth Sciences, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Upper-Ocean Lateral Heat Transports in the Niño3.4 Region and Their Connection with ENSO - He Zhao; Tongwen Wu; Laurent Z. X. Li; Fanghua Wu; Weihua Jie; Xiangwen Liu; Ronghua Zhang; Chengjun Xie (Journal of Meteorological Research, 2022)

Photoaging Characteristics of Disposable Masks under UV Irradiation - Xinhao Liu; Wei Cao; Linqing Xie; Chengjun Sun; Fenghua Jiang (Journal of Marine Science and Engineering, 2022)
The global outbreak of Corona Virus Disease 2019 (COVID-19) has led to an extreme increase in the use of disposable masks. If the used disposable masks are not appropriately disposed of, they will enter the natural environment and lead to environmental pollution. In order to understand the impacts of disposable masks after being disposed of into the natural environment, aging experiments with simulated natural conditions were performed on the outer, inner, and middle layers of the masks to verify the aging characteristics of disposable masks. We analyzed the mechanical behavior, surface morphology, and Fourier Transform Infrared Spectroscopy (FT-IR) spectra of disposable masks treated with different levels of UV irradiation to understand the possible changes in the masks under UV. Results showed that the elongation at break, tensile strength, and maximum force of all three polypropylene (PP) mask layers decreased after UV irradiation, indicating chemical bond breakage. In the process of photoaging, each layer of the disposable masks showed a different degree of microscopic surface changes after UV irradiation, and these changes gradually intensified with the extension of UV exposure time. FT-IR results showed that functional groups, such as hydroxyl and carbonyl groups increased in each layer after UV irradiation. The results of this study support that, although the different layers of the disposable masks are all made of PP, they age differently in the environment. With the ever-increasing number of disposable masks in the environment, we need to further study the aging and degradation of disposable masks to better understand their potential impacts on the environment in the future.

Levels of urinary metabolites of benzene compounds, trichloroethylene, and polycyclic aromatic hydrocarbons and their correlations with socioeconomic, demographic, dietary factors among pregnant women in six cities of China - Jing Zhu; Xuan Zhao; Mi Yang; Bo Zheng; Chengjun Sun; Xiaoli Zou; Zhen Liu; Kouji H. Harada (Environmental Science and Pollution Research, 2022)

Geochemistry and tectonic setting of Middle Ordovician MORB-like basalts in the Kunlun Orogen: implications for a back-arc environment - Ruibao Li; XianZhi Pei; Zuochen Li; Lei Pei; Youxin Chen; Chengjun Liu; Guochao Chen; Keng Feng (Arabian Journal of Geosciences, 2021)

Comparison of sedimentary organic carbon loading in the Yap Trench and other marine environments - Dong Li; Jun Zhao; Chenggang Liu; Chengjun Sun; Jianfang Chen; Jianming Pan; Zhengbing Han; Ji Hu (Journal of Oceanology and Limnology, 2020)

Water characteristics of abyssal and hadal zones in the southern Yap Trench observed with the submersible Jiaolong - Xuehai Liu; Yongzhi Liu; Wei Cao; Chengjun Sun (Journal of Oceanology and Limnology, 2020)

The latest tectonic magmatism in the Buqingshan–A’nyemaqen tectonic mélange belt: evidence from zircon U–Pb geochronology of intermediate–basic dikes, northern Tibetan Plateau, China - Zuochen Li; Xianzhi Pei; Ruibao Li; Lei Pei; Youxin Chen; Chengjun Liu; Zhanqing Liu; Guochao Chen; Meng Wang; Shaowei Zhao (Arabian Journal of Geosciences, 2019)

A generalized theory of the figure of the Earth: on the global dynamical flattening - Chengjun Liu; Chengli Huang; Yu Liu; Mian Zhang (Journal of Geodesy, 2019)

A generalized theory of the figure of the Earth: formulae - Chengli Huang; Yu Liu; Chengjun Liu; Mian Zhang (Journal of Geodesy, 2019)

Cambrian (~510 Ma) ophiolites of the East Kunlun orogen, China: A case study from the Acite ophiolitic tectonic mélange - Ruibao Li; XianZhi Pei; Zuochen Li; Lei Pei; Guochao Chen; Bo Wei; Youxin Chen; Chengjun Liu; Meng Wang (International Geology Review, 2018)

Removal of tetracyclines, sulfonamides, and quinolones by industrial-scale composting and anaerobic digestion processes - Hang Liu; Chengjun Pu; Xiaolu Yu; Ying Sun; Junhao Chen (Environmental Science and Pollution Research, 2018)

Complete genome sequence of Lactococcus lactis subsp. lactis SLPE1-3, a novel lactic acid bacterium causing postharvest decay of the mushroom Pleurotus eryngii - Yancun Zhao; Runjie Zhu; Ying Wang; Zhiwei Song; Chengjun Shan; Jingping Qiu; Fengquan Liu (Journal of Plant Pathology, 2018)

Validation of the quantitative trait locus underlying soybean plant height using residual heterozygous lines and near-isogenic lines across multi-environments - Long Yan; Yuanyuan Zhang; Qijian Song; Perry B. Cregan; Chunyan Yang; Yongqiang Charles An; Chengjun Wu; Qiang Chen; Bingqiang Liu; Rui Di; Mengchen Zhang (Euphytica, 2017)

Biomass, nutrient uptake and fatty acid composition of Chlamydomonas sp. ICE-L in response to different nitrogen sources - Meiling An; Yibin Wang; Fangming Liu; Xiaoqing Qi; Zhou Zheng; Naihao Ye; Chengjun Sun; Jinlai Miao (Acta Oceanologica Sinica, 2017)

Effects of red mud addition on cadmium accumulation in cole (Brassica campestris L.) under high fertilization conditions - Peng Li; Xianjia Peng; Zhaokun Luan; Tongke Zhao; Chengjun Zhang; Baocun Liu (Journal of Soils and Sediments, 2016)

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Acclimation of Antarctic Chlamydomonas to the sea-ice environment: a transcriptomic analysis - Chenlin Liu; Xiuliang Wang; Xingna Wang; Chengjun Sun (Extremophiles, 2016)

Influence of nitrogen form on the phytoextraction of cadmium by a newly discovered hyperaccumulator Carpobrotus rossii - Wuxing Liu; Chengjun Zhang; Pengjie Hu; Yongming Luo; Longhua Wu; Peter Sale; Caixian Tang (Environmental Science and Pollution Research, 2016)

Succulent species differ substantially in their tolerance and phytoextraction potential when grown in the presence of Cd, Cr, Cu, Mn, Ni, Pb, and Zn - Chengjun Zhang; Peter W. G. Sale; Gary J Clark; Wuxing Liu; Augustine I. Doronila; Spas D. Kolev; Caixian Tang (Environmental Science and Pollution Research, 2015)

Patterns and determinants of wood physical and mechanical properties across major tree species in China - JiangLing Zhu; Yue Shi; LeQi Fang; XingE Liu; ChengJun Ji (Science China Life Sciences, 2015)

Methodology for antibody preparation and detection of southern rice black-streaked dwarf virus - Zhuo Chen; Chengjun Yin; Jiaju Liu; Mengjiao Zeng; Zhenchao Wang; Dandan Yu; Liang Bi; Linhong Jin; Song Yang; Baoan Song (Archives of Virology, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Debris flow and landslide hazard mapping and risk analysis in China - Xilin Liu; Chengjun Yu; Peijun Shi; Weihua Fang (Frontiers of Earth Science, 2012)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)